(untitled) (Entrepreneurship Journal for Finance and Business, 2025)
Purpose of the research is to study the relationship between internal marketing and positive employee behavior, as well as to know the effect of the independent variable (internal marketing) on ​​the dependent variable (positive employee behavior). Design/Methodology: A simple random sample of (77) employees working in the Oil Products Distribution Company in Najaf Governorate was selected, and the questionnaire was used as a tool for collecting data. The researchers sought to know the nature of the relationship of influence between the research variables, and several statistical analyses of the data were adopted, including the Corinbach alpha, weighted, standard deviation, arithmetic mean, and regression analysis. Results: Through the current research, several conclusions were reached, including the existence of a statistically significant effect between the research variables (internal marketing and positive employee behavior).